Evaluation of Medical students perception on Personal Drug Selection for improving prospective Medical Education: A situational Analysis from Manipal College of Medical Sciences, Pokhara, Nepal - Banerjee, I; Saha, A; Sathian, B; Roy, B; Banerjee, I (Nepal Journal of Medical Sciences, 2015)
Background: Personal (P) drug selection is an important part of the pharmacology teaching and learning session. Most of the textbooks that are commonly followed by the medical schools of Nepal merely tell about the concepts of P drug selection. P drug selection lets students to think and make decisions about the drugs prescribed. The main objective of the study was to find the Medical students perspective of P- Drug selection from a medical college of Nepal. Methods: This cross sectional questionnaires based study was carried out at Manipal College of Medical Sciences, Pokhara, Nepal from July 2008- July 2013. Chi square test and Odds Ratio were used for analytical purpose. Questionnaire validation tests showed that the Alpha Cronbach was 0.72. Results: P drug selection is an important part of MBBS curriculum, which was reflected by 74.9% of the medical students. Most of the students, around 82% responded that P drug is for a disease and 85% students felt that time should be increased for the exercise. Around 90.1% students felt that P drug selection gives knowledge of the full chapter and 90.1% of the students found it difficult to find out the cost of the drugs from different brands. Conclusion: The overall views of medical students on P drug selection were positive. The teaching and learning activity of P Drug Selection needs improvement in certain areas. In this exercise a student learns the rationale drug usage for a particular disease objectively and in an unbiased manner. With proper amendments in the teaching and learning methodology of P drug selection students can think and make decisions about the prescription writing, furthermore can reduce the chances of irrational prescribing by the future doctors. Nepal Journal of Medical Sciences Vol.3(2) 2014: 89-93